2017
DOI: 10.4317/jced.54374
|View full text |Cite
|
Sign up to set email alerts
|

Preload loss of abutment screws after dynamic fatigue in single implant-supported restorations. A systematic review

Abstract: BackgroundTo carry out a systematic literature review of the causes of preload loss of the abutment screws, of internal and external connection implants, tightened to different torque values and subjected to cyclic loading.Material and MethodsA systematic search was conducted in PubMed, EMBASE, and Cochrane Library databases with reference to in vitro studies in which internal and external connection implants were subjected to cyclic loads to determine the degree of loosening of the abutment screws after loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 22 publications
2
35
0
6
Order By: Relevance
“…As many in vitro studies have reported, the friction between the abutment screw and the inner of the implant decreases after cyclic loading, and so does the torque. 19,36,37 A higher preload means a stronger resistance of the screw to loosening, and this slows down the process of screw loosening. 38,39 The preload is positively correlated with the value of the screw tightening torque.…”
Section: Introductionmentioning
confidence: 99%
“…As many in vitro studies have reported, the friction between the abutment screw and the inner of the implant decreases after cyclic loading, and so does the torque. 19,36,37 A higher preload means a stronger resistance of the screw to loosening, and this slows down the process of screw loosening. 38,39 The preload is positively correlated with the value of the screw tightening torque.…”
Section: Introductionmentioning
confidence: 99%
“…External hexagon connections have been shown to have rotational misfit in the range of 3 to 10°, while a rotational misfit of less than 2°is required to provide a stable screw joint that limits screw loosening (Binion, 1996a). Thus a disadvantage to the external hexagon connection includes a higher prevalence of screw loosening, which ranges from 6% to 48% (Levine et al, 1997;Pardal-Peláez and Montero, 2017), a higher prevalence of rotational misfit, a less esthetic result, and often, an inadequate microbial seal. Design modifications to improve abutment stability and fit and to limit rotational misfit have been applied to the height and width of the external hexagon.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, internal connection ( Figure 1b) allowed a better union between the implant and the abutment. Finally, morse taper connection (Figure 1c), which is another option for an internal connection, was introduced because of its improvement on screw loosening [14][15][16].…”
Section: Introductionmentioning
confidence: 99%